Physical Distance Tracking Jacket for Students with Special Needs - Mohamed Yusof, Anizam; Masleh, Nurul Syahirah; Ab. Rahman, Azmanirah (Research and Innovation in Technical and Vocational Education and Training, 2022)
The COVID-19 pandemic has affected all types and levels of learning including the education of students with special needs. Schools nationwide have taken the initiative to protect the safety and health of students by implementing home teaching and learning method, that can assist to reduce the transmission of virus by physical distancing. Therefore, a study was conducted aiming to develop a product that would assist students with special needs to attend school whilst prevent the transmission of COVID-19 virus. The main objective of this product development is to design a physical distance detector jacket for student with special needs based on the engineering design process (EDP) development model which involves four phases namely problem identification phase and problem research, making and selecting possible solutions, prototype development phase and product evaluation phase. This product uses an ultrasonic sensor to detect physical distance of less than one meter and gives a warning in three different ways to the students with special needs such as micro: bit display warning sign, buzzer sound, vibration from the back of the body by using vibration motor. The physical distance tracking jacket is suitable for vision impaired students, hearing impaired students and learning impaired students. The product would assist teachers to ensure that students with special needs would abide and comply to the physical distancing SOP during the teaching and learning process in school.